The Cleft-screen-questionnaire (CSQ) – A validated screening instrument for health-related quality of life in cleft patients. Issue 9 (September 2022) - Sander, A.K.; Dietrich, L.; Kloss-Brandstätter, A.; Krause, M.; Zimmerer, R.; Neuhaus, M.; Bartella, A.K.; Lethaus, B.
Summary: Background: The objective of this study is to develop and validate a specific screening instrument for assessing the quality of life (QoL) of patients with orofacial clefts. The Cleft-Screen-Questionnaire (CSQ) aims at identifying the main problematic areas and is intended for the routine use in everyday clinical practice to constantly evaluate the conditions' and treatments' effects on patients' well-being. Methods: First, a pool of 58 questions is created by collecting items from validated questionnaires previously used for assessing the QoL in cleft populations. After the removal of duplicate questions, the questionnaires are answered by 152 patients from a tertiary care center. A factor analysis followed by the calculation of Cronbach's alpha as a reliability measurement led to the final CSQ presented here. Results: The applied factor analysis resulted in five factors. Items showing low factor loadings (seen as <0.5) were excluded initially. Accordingly, factor analysis led to a preliminary number of 43 items. A reliability analysis using Cronbach's alpha and corrected alpha if item deleted showed an overall moderate to high reliability (seen as: 0.6–0.9). After excluding questions with increasing alphas if item deleted, analyses yielded in a final number of 38 questions. Conclusion: The final 38-item CSQ is a reliable instrument for evaluating the health-related QoL of cleft patients.